2012
DOI: 10.1007/s10753-012-9431-z
|View full text |Cite
|
Sign up to set email alerts
|

Nadroparin Sodium Activates Nrf2/HO-1 Pathway in Acetic Acid-Induced Colitis in Rats

Abstract: Effects of nadroparin sodium, a low molecular weight heparin, in colitis was investigated by analyzing proteins implicated in nuclear factor E2-related factor-2/heme oxygenase-1 (Nrf2/HO-1) and nuclear factor kappa B (NF-κB) pathways. Twenty-eight rats were used. Colitis was induced by acetic acid (AA). Nadroparin sodium was given to prevention and treatment groups in addition to AA. Colitis was assessed histologically and levels of proteins were analyzed with Western blot. Nadroparin not only prevented and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 47 publications
(56 reference statements)
1
18
0
Order By: Relevance
“…This effect may instead be due to the non-anticoagulant effects of lMWH (40). according to previous studies, nadroparin, which was used in the present study, has anti-inflammatory, anti-metastatic and anti-fibrotic activities (41)(42)(43)(44). Yalniz et al (44) reported that nadroparin exerts anti-oxidative and anti-inflammatory effects by regulating the nF-κB and nuclear factor erythroid 2-related factor 2/heme oxygenase 1 pathways.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This effect may instead be due to the non-anticoagulant effects of lMWH (40). according to previous studies, nadroparin, which was used in the present study, has anti-inflammatory, anti-metastatic and anti-fibrotic activities (41)(42)(43)(44). Yalniz et al (44) reported that nadroparin exerts anti-oxidative and anti-inflammatory effects by regulating the nF-κB and nuclear factor erythroid 2-related factor 2/heme oxygenase 1 pathways.…”
Section: Discussionmentioning
confidence: 63%
“…according to previous studies, nadroparin, which was used in the present study, has anti-inflammatory, anti-metastatic and anti-fibrotic activities (41)(42)(43)(44). Yalniz et al (44) reported that nadroparin exerts anti-oxidative and anti-inflammatory effects by regulating the nF-κB and nuclear factor erythroid 2-related factor 2/heme oxygenase 1 pathways. in contrast to tinzaparin, fondaparinux or to direct oral anticoagulants, enoxaparin increases the permeability of podocytes to albumin, as reported by delézay et al (45).…”
Section: Discussionmentioning
confidence: 63%
“…During high levels of ROS generation, oxidative modification of cysteine residues on Keap1 and phosphorylation of serine or threonine residues on Nrf2 result in the release of Nrf2 from Keap1, thereby escaping proteasomal degradation, allowing accumulation and translocation into the nucleus and binding to cis-acting ARE sites in promoters of antioxidant and phase II detoxifying genes (19). Although data of Nrf2 expression in the mucosa of IBD patients during active inflammation are not readily available, multiple rodent models of colitis have shown decreased colonic Nrf2 expression following induction of in- flammation that persists after inflammation has subsided (7,52,57). Nrf2 Ϫ/Ϫ mice show increased susceptibility to intestinal, liver, lung, kidney, and brain inflammation (8,24,25,40).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, using a medical-grade polyurethane tube for enteral feeding (external diameter 2 mm), 1~2 ml of (3~4%) acetic acid is instilled 6~8 cm proximal to the anus verge. Eventually, after 15~30 s of exposure the fluid is withdrawn and animals are sacrificed and their blood and colons are collected 24~48 hrs after induction of colitis for carrying out various histopathological and biochemical investigations [25,26,89,97,106,107,108]. Other scientists have revealed that intracolonic administration of 4 ml of 4 % acetic acid at a dose 5 ml/kg also leads to induction of colitis in rats [99,109,110,111,112].…”
Section: Chemical Induced Models Of Chronic Intestinal Inflammationmentioning
confidence: 99%